2016
DOI: 10.5191/jiaee.2016.23205
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale Farmers’ Perceptions of Agricultural Information Sources in Northern Haiti

Abstract: Agricultural extension in developing countries can be a major source of support for small-scale farmers. In Haiti, the majority of the agricultural population is made up of smallscale farmers. In the past, Haiti’s extension system has suffered from various governmental instabilities in the nation. This study sought to (a) determine the information channels smallscale farmers use in the North Department of Haiti, (b) determine the accessibility of quality information as perceived by small-scale farmers in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Several of these barriers could be addressed through farmer support by the MARNDR extension division. However, it does not appear farmers in the North Department have access to these services (Zeleya et al, 2016). There also appears to be some similarities to what Maiga et al (2016) found in West Africa.…”
Section: External Locus Of Controlmentioning
confidence: 66%
See 2 more Smart Citations
“…Several of these barriers could be addressed through farmer support by the MARNDR extension division. However, it does not appear farmers in the North Department have access to these services (Zeleya et al, 2016). There also appears to be some similarities to what Maiga et al (2016) found in West Africa.…”
Section: External Locus Of Controlmentioning
confidence: 66%
“…There is little research about farmer needs in Haiti. One recent study focused on small-scale producers in Northern Haiti (Zeleya, Harder, & Roberts, 2016). These researchers examined farmer access to timely information.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The lead researcher first read the statements multiple times to become immersed and gain a sense of the data as a whole (Creswell, 2005;Hsieh & Shannon, 2005). After gaining a deep understanding of the data, the lead researcher derived codes (Zelaya, Harder, & Roberts, 2016) by reading the data line by line for each respondent (Creswell, 2005;Hsieh & Shannon, 2005). Later, the derived codes were examined for any overlap or redundancy and finally merged together to develop broader themes (Creswell, 2005).…”
Section: Qualitative Data Collection and Analysismentioning
confidence: 99%
“…Haiti's extension services are barely seen throughout the country (Arias et al, 2013). Although regional agricultural assistance offices do exist within each of the ten departments, services are rarely provided to small-scale farmers (Zelaya, Harder, & Roberts, 2016). With little assistance, many farmers must independently make important decisions which will affect the outcomes of their livelihoods.…”
Section: Introductionmentioning
confidence: 99%